Detecção e análise molecular de Toxoplasma gondii e Neospora caninum em cães com distúrbios neurológicos - Langoni, Helio [UNESP]; Matteucci, Guilherme [UNESP]; Medici, Bruno [UNESP]; Camossi, Lucilene Granuzio [UNESP]; Richini-Pereira, Virgínia Bodelão [UNESP]; da Silva, Rodrigo Costa [UNESP] (FapUNIFESP (SciELO), 2012)
Introduction: Toxoplasma gondii and Neospora caninum are related Apicomplexa parasites responsible for systemic diseases in many species of animals, including dogs. Methods: This study aimed to determine the occurrence of T. gondii and N. caninum infections in 50 dogs with neurological signs that were admitted to the Veterinary Hospital of Universidade Estadual Paulista, City of Botucatu, Brazil. All animals were screened for antibodies using an immunofluorescent antibody test for both parasites. Tissues of positive animals were bioassayed in mice (T. gondii) and gerbils (N. caninum), and DNA was analyzed using the polymerase chain reaction (PCR). Positive samples for T. gondii by PCR were typed using restriction fragment length polymorphism-PCR for 11 markers: SAG1, SAG2 (5′-3′-SAG2 and alt.SAG2), SAG3, Btub, GRA6, L358, c22-8, c29-6, PK1 and Apico, and CS3 marker for virulence analysis. Results: Specific antibodies were detected in 11/50 (22%; 95% confidence interval (CI95%), 12.8-35.3%) animals for T. gondii and 7/50 (14%; CI95%, 7.02-26.3%) for N. caninum. In the bioassay and PCR, 7/11 (63.6%; CI95%, 34.9-84.8%) samples were positive for T. gondii and 3/7 (42.9%; CI95%I, 15.7-75.5%) samples were positive for N. caninum. Three different genotypes were identified, but only 1 was unique. Conclusions: These data confirm the presence of T. gondii and N. caninum in dogs from Brazil, indicating the importance of this host as a sentinel of T. gondii for human beings, and the genotypic variation of this parasite in Brazil.
Detection and molecular analysis of Toxoplasma gondii and Neospora caninum from dogs with neurological disorders
Keywords: Dogs; Genotypes; Neospora caninum; RFLP-PCR; Toxoplasma gondii; Zoonosis